Experimental and simulation evaluation of sulfate attack behavior of concrete in sulfate-rich and stray current environment - Yi Xu; Qian Chen; Zhisheng Lv; Li Cao; Yichao Chen; Sheng Jiang; Zhengyu Zhu; Hongqiang Chu; Linhua Jiang (Case Studies in Construction Materials)
The reinforced concrete structures within subway projects are often in a complex environment surrounded by the track's stray current and groundwater containing sulfate and chloride ions. These factors can contribute to concrete deterioration. The effects of current intensity and sulfate concentration on the sulfate resistance of concrete in subway engineering are investigated. The results indicate that the heightened current intensity can expedite sulfate ions migration, leading to the formation of swelling hydration products and pore refinement. Despite elevated sulfate concentration can also stimulate hydration, its effectiveness is not on par with that of increased current intensity. Moreover, phase analysis demonstrates a diminish in diffraction peak intensity for calcium hydroxide due to current, indicating the decomposition of calcium hydroxide. Pore analysis reveals that the current reduces harmful pores and improves concrete compactness and durability. Finite element analysis provides a basis for evaluating concrete's resistance to sulfate attacks in subway engineering.